Use of Ganciclovir in the Treatment of Acquired Cytomegalovirus Disease in a Preterm Infant - H Amin; T Jadavji; R Sauve; J Gill (Canadian Journal of Infectious Diseases)
The first use of ganciclovir in a preterm infant is reported. The 27 week appropriate-for-gestational-age male infant developed a disseminated cytomegalovirus infection subsequent to a blood transfusion. A daily dose of 10 mg/kg administered intravenously in two divided doses for a total of 14 days was given without adverse clinical or toxic effects. The patient has remained well following discharge from hospital.